1997
DOI: 10.1021/ic9703336
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Oxygenation Catalysts. 3.1 Thermodynamic Characterization of Electron Transfer and Solvent Exchange Reactions of Co(salen)/[Co(salen)]+ in DMF, Pyridine, and Their Mixtures

Abstract: Redox and ligand exchange reactions of the oxygenation catalyst (N,N '-bis(salicylidene)ethylenediaminato)cobalt(II), Co(salen), and its one-electron oxidation product, Co(salen)(+), are investigated in DMF, pyridine, and mixtures of these solvents. Electron transfers and solvent exchange reactions involving three neutral Co(II) and three cationic Co(III) complexes with different axially bound solvent molecules (two DMF, one DMF and one pyridine, or two pyridine molecules) form a three-rung ladder scheme. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Organic substrates containing donor atoms (phenols, indoles, and amines) are more easily oxidized. 39 As in Nature, Schiff base metal complexes were designed to include a cavity, in order to accommodate dioxygen or some small ligands. 40 However, as already presented in this review, non-covalent secondary interactions are essential in order to obtain selective and efficient catalysts with Salen metal complexes.…”
Section: Manganese and Chromium Schiff Basesmentioning
confidence: 99%
“…Organic substrates containing donor atoms (phenols, indoles, and amines) are more easily oxidized. 39 As in Nature, Schiff base metal complexes were designed to include a cavity, in order to accommodate dioxygen or some small ligands. 40 However, as already presented in this review, non-covalent secondary interactions are essential in order to obtain selective and efficient catalysts with Salen metal complexes.…”
Section: Manganese and Chromium Schiff Basesmentioning
confidence: 99%
“…The electrochemical studies of cobalt(II) Salen type Schiff bases showed that the major species in the solution were Co(Schiff baes)(Solvent) 2 in DMF and DMSO [6,8]. The following redox reaction is proposed for Co(II) BBE complex in dimethylformamide [12,[23][24][25].…”
Section: The Effect Of Metal Ions On Oxidation Potentialsmentioning
confidence: 99%
“…Cyclic voltammetry has been a useful instrument to study the mechanisms of the catalysis property of metal Schiff base complexes and their reactivity [2,[4][5]. To explore the catalytic activity, the electrochemical properties of Co(III) BAE and Salen Schiff base complexes were studied intensively [6][7][8][9][10][11][12]. Also, the electrochemical *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some Schiff complexes find different application areas. For example, such as the oxidation of platinum complexes, the use of oxygen as the oxygen carrier model for cobalt complex oxygenation and transport reactions, the oxidation of phenols and olefins catalytic reactions, the use of Mn and Ru complexes in water catalyzed photolysis, and iron complexes catalyzed by cathodic oxygen which is known to be used as a catalyst . The catalytic activity of complexes of Schiff’s complexes with transition metal ions has also shown considerable interest in some industrial and biochemical events …”
Section: Introductionmentioning
confidence: 99%